I have this problem: find by power series with respect to $y$ the solution of the Cauchy problem

\begin{cases} u_{yy}=u_{xx}+u\\ u(x,0)=e^x\\ u_y(x,0)=0 \end{cases} I know that the solution has the form $\sum_{n=0}^{\infty}a_n(x)y^n$ and by initial conditions I found that $a_0(x)=e^x$ and that $a_1(x)=0$, but I cannot continue and conclude...

(P.S.: differentiating $u(x,0)$ with respect to $x$ I found that $a^{(k)}_0(x)=e^x$ with $k\geq0$ and it's ok. Moreover differentiating $u_y(x,0)$ w.r.t. $y$, we found that $u_{yy}(x,0)=u_{yyy}(x,0)=\ldots=0$ but I cannot take advantage of this..)

Thanks :)


Differentiating term by term, you got: $$\begin{split} u(x,y) &= \sum_{n=0}^\infty a_n(x)\ y^n\\ u_{xx}(x,y) &= \sum_{n=0}^\infty a_n^{\prime \prime} (x)\ y^n\\ u_{y}(x,y) &= \sum_{n=0}^\infty (n+1)a_{n+1}(x)\ y^n\\ u_{yy}(x,y) &= \sum_{n=0}^\infty (n+2)(n+1)a_{n+2}(x)\ y^n\end{split}$$ and plugging these relations both in the PDE and in the initial conditions yields: $$\begin{cases} \sum_{n=0}^\infty (n+2)(n+1)a_{n+2}(x)\ y^n = \sum_{n=0}^\infty \big( a_n^{\prime \prime} (x) +a_n(x)\big)\ y^n\\ a_0(x) = e^x \\ a_1(x) = 0\; ,\end{cases}$$ which translates into a system of recurrence equations (involving also second derivatives) for the $a_n$s, namely: $$\tag{R} \begin{cases} (n+2)(n+1)a_{n+2}(x) = a_n^{\prime \prime} (x) +a_n(x)\\ a_0(x) = e^x \\ a_1(x) = 0\; .\end{cases}$$ Recurrence (R) is second order with the RHside which does not depend on $a_{n+1}$; therefore, it separates the $a_n$s depending on odd indices from the $a_n$s depending on even indices. In particular, if $n=2h+1$ you get: $$\begin{cases} (2h+3)(2h+2)a_{2h+3}(x) = a_{2h+1}^{\prime \prime} (x) +a_{2h+1}(x)\\ a_1(x) = 0\; ,\end{cases}$$ from which it follows: $$a_{2h+1}(x) = 0\quad \text{for all } h\in \mathbb{N};$$ on the other hand, if $n=2h$ you get: $$\begin{cases} (2h+2)(2h+1)a_{2h+2}(x) = a_{2h}^{\prime \prime} (x) +a_{2h}(x)\\ a_0(x) = e^x\; ,\end{cases}$$ from which it follows: $$\begin{split} a_0(x) &= e^x\\ a_{2}(x) &= \frac{1}{2!}\ \big(a_0^{\prime \prime} (x) +a_0(x)\big)\\ &= \frac{2}{2!}\ e^x\\ a_{4}(x) &= \frac{1}{4\cdot 3}\ \big(a_{2}^{\prime \prime} (x) +a_{2}(x)\big) \\ &= \frac{4}{4!}\ e^x\\ a_{6}(x) &= \frac{1}{6\cdot 5} \big( a_{4}^{\prime \prime} (x) +a_{4}(x)\big)\\ &= \frac{8}{6!}\ e^x\end{split}$$ and in general: $$a_{2h}(x) = \frac{2^h}{(2h)!}\ e^x\quad \text{for all } h\in \mathbb{N}.$$

Hence: $$u(x,y) = \sum_{h=0}^\infty \frac{2^h}{(2h)!}\ e^x\ y^{2h} = e^x\ \cosh(\sqrt{2}\ y)$$ is the unique solution of your IVP.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.